2010
DOI: 10.1093/ndt/gfq304
|View full text |Cite
|
Sign up to set email alerts
|

Calcium, phosphorus, PTH and death rates in a large sample of dialysis patients from Latin America. The CORES Study

Abstract: In summary, in 16,173 HD patients, elevated and reduced serum levels of albumin-corrected calcium, phosphorus and PTH levels were associated with increments in all-cause mortality. Similar results were obtained when only cardiovascular mortality was analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 39 publications
10
88
2
2
Order By: Relevance
“…All of these factors contribute to regulating the renal tubular phosphate reabsorption capacity and might explain the lower phosphate excretion and then the higher serum phosphate level observed in women than in men [30]. The literature about the association we found between hyperphosphatemia and diabetic nephropathy is largely conflicting: some investigators report similar result to ours [21,23,31] but others describe the opposite, with less hyperphosphatemia in diabetic CKD patients [9,10,19]. Additional studies are warranted to evaluate the precise link between diabetes and phosphatemia and its mechanism.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…All of these factors contribute to regulating the renal tubular phosphate reabsorption capacity and might explain the lower phosphate excretion and then the higher serum phosphate level observed in women than in men [30]. The literature about the association we found between hyperphosphatemia and diabetic nephropathy is largely conflicting: some investigators report similar result to ours [21,23,31] but others describe the opposite, with less hyperphosphatemia in diabetic CKD patients [9,10,19]. Additional studies are warranted to evaluate the precise link between diabetes and phosphatemia and its mechanism.…”
Section: Discussionsupporting
confidence: 51%
“…The association between hyperphosphatemia and lower age is now well recognized, as it has been shown in several previous studies in different settings: in the community setting, this association was found in a general population [19], a diabetic population [20], and a CKD population [21]; in the hospital setting, the association was shown in vascular patients scheduled for major surgery [22] and also in a dialysis population [9,10]. Various mechanisms may explain this association, including increased undernutrition with age, decreased renal phosphate reabsorption, and hormonal factors.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is also important to emphasize that classic US KDOQI limits between 150 and 300 pg/ml have been associated (88,89). Therefore, some authors and guidelines continue to recommend these "old" targets, or even lower ones (90), although a correction of PTH values for the kit utilized is currently advised in order to take into account the great variability in PTH assays (i.e., approximately 2-5 times the upper limit of normality for a particular PTH assay) (6,7,(91)(92)(93).…”
Section: Pth Oversuppressionmentioning
confidence: 99%
“…Given the striking baseline differences in key parameters, it was impossible to draw a firm conclusion about the costeffectiveness of the DD protocol. At baseline, the DD group had the highest MIS and serum phosphorus, which reportedly predict increased mortality, days and frequency of hospitalization, as well as lower QOL [5,[64][65][66][72][73][74][75]. These factors made it practically impossible for intensive nutrition education to be cost-effective.…”
Section: Trial-based Economic Evaluationmentioning
confidence: 99%